The Effects of Climate Change on the Value of Groundwater Dependent Ecosystems: The Rokua Esker, Northern Finland - Phoebe Koundouri; Marva Stithou; Eva Kougea; Pertti Ala-Aho; Riku Eskelinen; Timo Karjalainen; Bjorn Klove; Manuel Pulido-Velazquez; Kalle Reinikainen; Pekka Rossi
Rokua in Northern Finland is a groundwater dependent ecosystem very sensitive to climate change and natural variability. As such, the water level of most of the lakes is a function of the level of the groundwater table of the esker which is naturally recharged. This chapter presents results from an application of a choice experiment and contingent valuation method regarding ground water quantity. General publicÃƒÂ¢ïÂ¿Â½ïÂ¿Â½s elicited values highlight the importance of water management policy which contributes to the sustainability of groundwater dependent ecosystems. Choice experiment, Contingent valuation, Climate change, Water quantity, Groundwater dependent ecosystems.